Carbon heterogeneities in austenite during Quenching & Partitioning (Q&P) process revealed by in situ High Energy X-Ray Diffraction (HEXRD) experiments. (May 2020) - Allain, Sébastien Y.P.; Gaudez, Steve; Geandier, Guillaume; Danoix, Frédéric; Soler, Michel; Goune, Mohamed
Abstract: Based on the evolution of the positions and intensities of the diffraction peaks, high energy X-ray diffraction (HEXRD) is recognized as the ultimate method to follow quantitatively in situ phase transformations in steels. However, the possible asymmetricity of diffraction peaks is seldom considered, and is known to bear information. A procedure for quantifying their skewness is proposed. In the case of a third generation high strength steel obtained by quench and partitioning (Q&P), the skewness is shown to be due to carbon heterogeneities at austenite/martensite interfaces developed at nanoscale, in agreement with prior post mortem atom probe tomography (APT) investigations. Graphical abstract: Image, graphical abstract